The “Promised Land” Claim in the Legitimacy of the Israeli Occupation: Examining the Relevance of Max Weber's Theory of Authority - Zaid Tsabit Al Kalatini; Asep Abdul Sahid; Muhammad Izzuddin Al Haq (Jurnal Iman dan Spiritualitas, 2025)
This study aims to examine the relevance of Weber's theory of authority in relation to the phenomenon of the Promised Land claim and its impact on the legitimacy of the Israeli occupation. The results and discussion in this study show that the Zionist political movement successfully utilised Jewish theological themes as the basis for the establishment of the state of Israel, in this case, the Promised Land claim becomes a doctrine that functions as a political aspiration and is believed to be rooted in divine and religious authority, revealing that Weberian tripartite classification of authority have limitations in explaining the form of legitimacy that comes from theological claims. The conclusion of this study is that the the Promised Land claim effectively functions as theological legitimacy in the Israeli occupation, offering a new form of authority distinct from Weberian tripartite classification of authority (traditional, charismatic, rational-legal).